2023
DOI: 10.2169/internalmedicine.8944-21
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Japanese Hospitalist System for Patients with Urinary Tract Infection: A Propensity-matched Analysis

Abstract: Objective The hospitalist system in the United States has been considered successful in terms of the quality of care and cost effectiveness. In Japan, however, its efficacy has not yet been extensively examined. This study examined the impact of the hospitalist system on the quality of care and healthcare economics in a Japanese population using treatment of urinary tract infection as an example. Methods We analyzed 271 patients whose most resource-consuming diagnosis at admission was urinary tract infection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… 14 The evidence supporting the clinical benefits of GM is currently limited, with most evidence regarding cost reduction and improvement in quality of care derived from small-scale, single-center studies. 15 , 16 These studies cover a range of clinical areas, including improved quality of inpatient care for infectious endocarditis, 17 increased blood culture collection rate, 18 shortened length of hospital stay, 19 improved quality of home medical care, 20 COVID-19 care, 21 compensating for the shortage of specialists, 22 and improved heart failure management. 23 Studies have been conducted on the patient population, locations, and clinical skills covered during GM training.…”
mentioning
confidence: 99%
“… 14 The evidence supporting the clinical benefits of GM is currently limited, with most evidence regarding cost reduction and improvement in quality of care derived from small-scale, single-center studies. 15 , 16 These studies cover a range of clinical areas, including improved quality of inpatient care for infectious endocarditis, 17 increased blood culture collection rate, 18 shortened length of hospital stay, 19 improved quality of home medical care, 20 COVID-19 care, 21 compensating for the shortage of specialists, 22 and improved heart failure management. 23 Studies have been conducted on the patient population, locations, and clinical skills covered during GM training.…”
mentioning
confidence: 99%
“…On the practical side, Hamada et al showed that hospitalists improve the care of patients with urinary tract infection ( 6 ). Other research from Japanese groups also demonstrated that the length of hospital stay was significantly shortened after the introduction of a hospital medicine department (adjusted difference -0.659 days; 95% confidence interval -1.118 to -0.136; p=0.01) ( 7 ).…”
mentioning
confidence: 99%